Lithium ion battery and electric device

By using electrolyte with high lithium salt concentration and appropriate density in lithium-ion batteries and selecting suitable solvents, the problem of concentration polarization in fast-charge lithium-ion batteries is solved, and the circulation performance and energy density of the battery are improved.

CN119833759APending Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410303348.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There is a severe polarization of the concentration difference during the charging process of fast-charging lithium-ion batteries, which leads to a cycle dive, affecting service life and stability.

Method used

An electrolyte with a lithium salt concentration of more than or equal to 1 mol/L and a density of 0.9 g/mL to 1.23 g/mL was used, and carbonate solvents with low viscosity and high dielectric constant and carboxylate solvents with high ionic conductivity and low density were selected as solvents for the electrolyte to improve the density and conductivity of the electrolyte and reduce the concentration difference polarization.

Benefits of technology

When fast charging conditions are met, the circulation performance and volume energy density of lithium-ion batteries are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833759A_ABST
    Figure CN119833759A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a lithium ion battery and a power utilization device, the lithium ion battery comprises an electrolyte, the electrolyte comprises a lithium salt, and the concentration c of the lithium salt in the electrolyte meets the condition that c is greater than or equal to 1 mol / L; the density rho of the electrolyte is greater than or equal to 0.9 g / mL and less than or equal to 1.23 g / mL; the charging time t of charging the lithium ion battery from 10% SOC to 80% SOC is greater than or equal to 8.8 min and less than or equal to 15 min. The lithium ion battery has good fast charge capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a lithium-ion battery and an electrical device. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, and have thus achieved great development.

[0003] As people continue to pursue efficiency in life, fast-charging lithium-ion batteries have become a focus of development. The concentration polarization of lithium-ion batteries during fast charging is more serious than that of ordinary lithium-ion batteries, causing lithium-ion battery cycle polarization to drop, seriously threatening the service life and cycle stability of fast-charging lithium-ion batteries. Therefore, how to improve the cycle performance of fast-charging lithium-ion batteries is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above technical problems, and its purpose is to provide a lithium ion battery and an electrical device. The lithium ion battery has a fast charging capability and can have good cycle performance under fast charging.

[0005] In a first aspect, a lithium ion battery is provided, comprising: an electrolyte, the electrolyte comprising a lithium salt, the concentration c of the lithium salt in the electrolyte satisfying: c ≥ 1 mol / L; the density ρ of the electrolyte satisfying: 0.9 g / mL ≤ ρ ≤ 1.23 g / mL; and the charging time t of the lithium ion battery from 10% SOC to 80% SOC satisfying: 8.8 min ≤ t ≤ 15 min.

[0006] In the embodiments of the present application, the lithium-ion battery can be charged from 10% SOC to 80% SOC in 8.8 min to 15 min. In other words, the lithium-ion battery is a fast-charge lithium-ion battery. Moreover, the fast-charge lithium-ion battery includes an electrolyte with a larger lithium salt concentration and a lower density. The larger electrolyte concentration and the lower electrolyte density can improve the concentration polarization of the lithium-ion battery during the fast-charge process, thereby improving the cycle performance of the fast-charge lithium-ion battery.

[0007] In one possible implementation, c≤1.8 mol / L.

[0008] In one possible implementation, 1.1 mol / L≤c≤1.6 mol / L.

[0009] In one possible implementation, 8.8 min≤t≤10 min.

[0010] In a possible implementation, the electrolyte includes a first solvent, and the first solvent includes at least one of ethylene carbonate, propylene carbonate, and ethyl methyl carbonate.

[0011] In the embodiments of the present application, by selecting a carbonate solvent with low viscosity and high dielectric constant as the first solvent, it is beneficial to the rapid migration of lithium ions in the electrolyte and the solubility of lithium salts in the electrolyte, thereby helping to improve the polarization of the lithium-ion battery during fast charging and enhance its stability during the cycle.

[0012] In a possible implementation, the electrolyte includes a second solvent, and the second solvent includes R1-COO-R2, wherein R1 and R2 each independently include one of an alkyl group having 1 to 5 carbon atoms and a halogenated alkyl group having 1 to 5 carbon atoms.

[0013] In the embodiments of the present application, by selecting a carboxylic acid ester solvent with high ionic conductivity and low density as the second solvent, it helps to improve the density and conductivity of the regulated electrolyte, so that the electrolyte is compatible with the fast charging capability of the lithium-ion battery, thereby obtaining a lithium-ion battery with both fast charging capability and good cycle stability.

[0014] In a possible implementation, the mass content X of the first solvent in the electrolyte satisfies: 20%≤X≤30%.

[0015] In a possible implementation, the mass content Y of the second solvent in the electrolyte satisfies: 20%≤Y≤60%.

[0016] In one possible implementation, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0017] In a possible implementation, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium bis(fluorosulfonyl)imide in the electrolyte is less than or equal to 30%.

[0018] In the embodiments of the present application, by selecting a mixture of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide as the lithium salt and controlling the concentration ratio of lithium bis(fluorosulfonyl)imide, the possibility of electrode plates being corroded by the electrolyte can be reduced while improving the low temperature performance of the lithium-ion battery.

[0019] In a possible implementation, the conductivity σ of the electrolyte satisfies: 13 mS / cm≤σ≤20 mS / cm.

[0020] In a possible implementation, the viscosity μ of the electrolyte satisfies: 2.2 cP≤μ≤2.7 cP.

[0021] In a possible implementation, the volume energy density VED of the lithium-ion battery satisfies: VED ≥ 400Wh / L.

[0022] In a possible implementation, the lithium-ion battery includes a negative electrode plate, the negative electrode plate includes a negative electrode film layer; the single-side coating weight CW of the negative electrode film layer on the negative electrode plate satisfies: 0.06 mg / mm 2 ≤CW≤0.13mg / mm 2 .

[0023] In one possible implementation, 0.08 mg / mm 2 ≤CW≤0.115 mg / mm 2 .

[0024] In a possible implementation, the compaction density PD of the negative electrode film layer satisfies: 1.4 g / cc≤PD≤1.75 g / cc.

[0025] In one possible implementation, 1.55 g / cc ≤ PD ≤ 1.7 g / cc.

[0026] In a possible implementation, the lithium-ion battery includes a positive electrode plate, the positive electrode plate includes a positive electrode film layer; the single-sided coating weight CW' of the positive electrode film layer on the positive electrode plate satisfies: 0.13 mg / mm 2 ≤CW'≤0.29 mg / mm 2 .

[0027] In one possible implementation, 0.19 mg / mm 2 ≤CW'≤0.26 mg / mm 2 .

[0028] In a possible implementation, the compaction density PD' of the positive electrode film layer satisfies: 2.5 g / cc≤PD'≤2.9 g / cc.

[0029] In one possible implementation, 2.6 g / cc≤PD'≤2.8 g / cc.

[0030] In a second aspect, an electrical device is provided, wherein the electrical device comprises a lithium-ion battery in any possible implementation of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0032] Figure 1 A schematic diagram of a battery cell.

[0033] Figure 2 A schematic diagram of a battery module.

[0034] Figure 3 A schematic diagram of a battery.

[0035] Figure 4 Another schematic diagram of a battery. DETAILED DESCRIPTION

[0036] Hereinafter, the embodiments of the lithium-ion battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] In the description of the present application, it should be noted that, unless otherwise specified, "multiple" means more than two; the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "inner", "outer", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0039] If not specifically stated, in this application, the phrase "A and / or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A and / or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.

[0043] Next, embodiments of the present application are introduced.

[0044] In recent years, secondary batteries have been widely used in power tools, electronic products, electric vehicles, aerospace and other fields due to their high energy density and long service life, and have achieved great development. Usually, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. Among them, the electrolyte plays a role in conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which allows active ions to pass through while preventing the positive and negative electrodes from short-circuiting, so that the electrochemical reaction of the secondary battery proceeds normally.

[0045] Take lithium-ion batteries as an example. Lithium-ion batteries are a typical secondary battery. Because they rely on the chemical reaction of lithium ions intercalating and disintercalating between the positive and negative electrodes for charging and discharging, lithium-ion batteries are also called rocking-chair batteries. During the charging process of lithium-ion batteries, lithium ions are released from the positive electrode active material, move to the negative electrode through the conduction of the electrolyte and embed into the negative electrode active material; and during the discharge process, lithium ions are released from the negative electrode active material, move to the positive electrode through the conduction of the electrolyte and embed into the positive electrode active material.

[0046] It should be understood that the "lithium insertion" and "embedding" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "extraction", "delithium" and "extraction" processes described in this application refer to the process in which lithium ions are extracted from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.

[0047] As the application scope of lithium-ion batteries becomes wider and wider, and the use scenarios become more and more diverse, new requirements are put forward for the charging capacity of lithium-ion batteries. For example, for power vehicles, mileage anxiety and long charging time have become the main problems hindering their development. Therefore, the fast charging (FC) capability is called an important goal for the development of lithium-ion batteries. Fast charging is referred to as fast charging, which refers to charging the battery to a full or nearly full state in a short period of time. The industry in different regions has different standards for the specific definition of fast charging. Generally speaking, if the battery can be charged to 80% of its full power in 0.5 h~2 h, it is considered to be fast charging. Furthermore, a charging time of less than 10 min can be considered to be in the range of extreme fast charging (XFC). However, studies have shown that low temperature and high rate charging can cause rapid attenuation of battery capacity, output power and other performance. Therefore, in addition to meeting the requirements of fast charging, fast charging batteries also need to achieve a certain cycle life and meet relevant safety performance and electrical performance. In the embodiment of the present application, a fast charging lithium-ion battery refers to a lithium-ion battery with fast charging capability.

[0048] For lithium-ion batteries, concentration polarization is an important reason for the increase of internal resistance, decrease of capacity, slow charging speed and cycle drop of lithium-ion batteries. Concentration polarization is the result of the combined action of multiple factors inside lithium-ion batteries. One of the reasons is that the uneven distribution of lithium ion concentration in the electrolyte leads to inconsistent electrolyte conductivity at different positions inside the lithium-ion battery. For example, during the charging process, the active materials in the thickness direction of the positive and negative pole pieces will undergo ion diffusion due to electrochemical reactions and other reasons, and there is a certain concentration difference in itself. In the thickness direction of the positive and negative pole pieces, the degree of electrolyte infiltration is also different, which further increases the difference in lithium ion concentration and aggravates the concentration polarization in the thickness direction of the positive and negative pole pieces. For another example, in actual use, lithium-ion batteries will be fixed and placed, so under the influence of gravity, the lithium ion concentration distribution in the electrolyte is also uneven. In other words, the "lower" the position along the gravity direction, the greater the concentration of lithium ions, resulting in concentration polarization of lithium-ion batteries in the gravity direction.

[0049] For fast-charging lithium-ion batteries, under the conditions of high current density or high charging rate, concentration polarization is more serious than that of ordinary lithium-ion batteries, and there is a cycle accumulation phenomenon, which causes the capacity of fast-charging lithium-ion batteries to decay rapidly and drop in cycles, seriously affecting the practical application of fast-charging lithium-ion batteries.

[0050] In view of this, the embodiment of the present application provides a lithium-ion battery and an electrical device, wherein the lithium-ion battery has a fast charging capability of being charged from 10% SOC to 80% SOC in a time of less than or equal to 15 minutes, and comprises an electrolyte having a lithium salt concentration greater than or equal to 1 mol / L and a density ρ of 0.9 g / mL to 1.23 g / mL. The larger lithium salt concentration of the electrolyte can improve the concentration polarization in the thickness direction of the positive and negative pole pieces of the lithium-ion battery during the fast charging process, and the lithium salt concentration also affects the density, viscosity and conductivity of the electrolyte, and the density, viscosity and conductivity of the electrolyte will affect the lithium ion dynamics; while the smaller electrolyte density helps to improve the conductivity of the electrolyte to balance the effect of the lithium salt concentration on the lithium ion dynamics, and can improve the concentration polarization in the gravity direction of the lithium-ion battery during the fast charging process, thereby, the lithium-ion battery not only has excellent fast charging performance, but also has good cycle performance.

[0051] It should be understood that the above fast charging capability is the fast charging capability of lithium-ion batteries at 25°C to 35°C. During the fast charging process of lithium-ion batteries, the current density (or rate) is usually not constant, but variable.

[0052] In one possible implementation, the charging time of a lithium-ion battery from 10% SOC to 80% SOC is less than or equal to 15 min when the current density is greater than or equal to 2.8 C. The current density is the equivalent current density of the lithium-ion battery during the process of charging from 10% SOC to 80% SOC. In other words, during the process of charging from 10% SOC to 80% SOC, the current density I may gradually decrease from greater than 2.8 C to less than 2.8 C. In this process, the lithium-ion battery may undergo a transition from constant current charging to constant voltage charging, and thus, the current density is not constant. For example: start charging the lithium-ion battery at room temperature of 25 ° C, charge from 10% SOC to 80% SOC, and the charging time is 10 minutes (equivalent current I ≥ 4C). The charging process is: initially at 5 C from 10% SOC to 45% SOC, then at 4.6 C from 45% SOC to 50% SOC, 4.3 C from 50% SOC to 55% SOC, 3.9 C from 55% SOC to 60% SOC, 3.6 C from 60% SOC to 65% SOC, 3.3 C from 65% SOC to 70% SOC, 3.1 C from 70% SOC to 75% SOC, 2.9 C from 75% SOC to 80% SOC, and the charging is completed. The charging time for lithium-ion batteries from 0% SOC to 100% SOC at 1C is 60 min. Therefore, when the charging time of the lithium-ion battery from 10% SOC to 80% SOC is measured to be 10 min, the equivalent current density of the process can be calculated as: [(80% SOC-10% SOC) / (100% SOC-0% SOC)]×[(1C×60 min) / 10 min]=4.2 C.

[0053] If a lithium-ion battery is placed on a charging station for charging, the time it takes to charge from 0% SOC to 100% SOC can also be directly recorded. For example, if the time is around 15 minutes (with an error of no more than 1 minute), it is generally considered to be a 4 C fast-charged battery. For another example, if the time is around 12 minutes (with an error of no more than 1 minute), it is generally considered to be a 5 C fast-charged battery. For another example, if the time is around 10 minutes (with an error of no more than 1 minute), it is generally considered to be a 6 C fast-charged battery.

[0054] Generally, a lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. Next, the lithium-ion battery provided in the present application and various parts of the lithium-ion battery are introduced.

[0055] First, a lithium-ion battery is provided. The lithium-ion battery includes an electrolyte, the electrolyte includes a lithium salt, and the concentration c of the lithium salt in the electrolyte satisfies: c≥1 mol / L; the density ρ of the electrolyte satisfies: 0.9 g / mL≤ρ≤1.23 g / mL; and the charging time t of the lithium-ion battery from 10% SOC to 80% SOC satisfies: 8.8 min≤t≤15 min.

[0056] During the fast charging process of lithium-ion batteries, there is a serious concentration polarization of lithium ions in the thickness direction of the positive and negative pole pieces and in the direction of gravity, which may cause lithium deposition locally on the negative pole piece of the lithium-ion battery in severe cases. In the embodiments of the present application, the lithium-ion battery has a fast charging capability, and the lithium-ion battery includes an electrolyte with a relatively high lithium salt concentration and a relatively low density. A relatively high lithium salt density helps to increase the transfer rate of lithium ions in the electrolyte, and helps to diffuse lithium ions in the thickness direction of the positive and negative pole pieces, thereby improving the concentration polarization in the thickness direction of the positive and negative pole pieces; a relatively low density makes the electrolyte "lighter", which can reduce the difficulty of lithium ions "climbing" in the direction of gravity, facilitates the infiltration of the electrolyte into the positive and negative pole pieces in the direction of gravity, and increases the lithium ion transfer rate in the direction of gravity. As a result, the lithium-ion battery of the present application can obtain good cycle performance while meeting the fast charging conditions.

[0057] It should be understood that the concentration c of the lithium salt and the density ρ of the electrolyte can be controlled by controlling the amount of lithium salt added when preparing the electrolyte, selecting a suitable solvent and controlling its ratio; the charging time t of the lithium-ion battery can be regulated by controlling the charging current of the lithium-ion battery.

[0058] In one embodiment, c≤1.8 mol / L; optionally 1.1 mol / L≤c≤1.6 mol / L.

[0059] For example, c can be 1.1 mol / L, 1.15 mol / L, 1.2 mol / L, 1.25 mol / L, 1.3 mol / L, 1.35 mol / L, 1.4 mol / L, 1.45 mol / L, 1.5 mol / L, 1.55 mol / L, 1.6 mol / L, 1.65 mol / L, 1.7 mol / L, 1.75 mol / L, 1.8 mol / L, or its value is within the range obtained by combining any two of the above values.

[0060] If the lithium salt concentration in the electrolyte is too low, the improvement effect on concentration polarization is limited, while if the concentration is too high, the viscosity of the electrolyte will increase, affecting the migration rate of lithium ions in the electrolyte. Therefore, in this embodiment, by controlling the lithium salt concentration within the above range, it is helpful to improve the lithium ion concentration polarization while making the electrolyte have a more appropriate viscosity.

[0061] In one embodiment, 0.9 g / mL≤ρ≤1.23 g / mL; optionally, 1.105 g / mL≤ρ≤1.22 g / mL.

[0062] Specifically, p can be 0.9 g / mL, 0.92 g / mL, 0.94 g / mL, 0.96 g / mL, 0.98 g / mL, 1 g / mL, 1.02 g / mL, 1.04 g / mL, 1.06 g / mL, 1.08 g / mL, 1.1 g / mL, 1.12 g / mL, 1.14 g / mL, 1.16 g / mL, 1.18 g / mL, 1.2 g / mL, 1.22 g / mL, 1.23 g / mL, or its value is within the range obtained by combining any two of the above values.

[0063] If the density of the electrolyte is too high, the electrolyte is "heavy", making it difficult for the electrolyte to infiltrate and reabsorb the positive and negative electrodes in the direction of gravity. During the fast charging process, the concentration difference of lithium ions in the direction of gravity is large, which aggravates the concentration polarization in the direction of gravity and is not conducive to the cycle performance of the lithium-ion battery. If the density is too low, the volume of the electrolyte is large under the same mass, causing the injection coefficient of the lithium-ion battery (unit g / Ah) to decrease, which may cause the lithium-ion battery to be unable to inject enough electrolyte, resulting in a cycle jump. Therefore, this embodiment can further improve the cycle performance of the lithium-ion battery by controlling the density of the electrolyte within an appropriate range.

[0064] In one embodiment, 8.8 min≤t≤10 min. That is, the lithium-ion battery provided in the present application also has the ability to support extremely fast charging within ten minutes or less.

[0065] In one embodiment, the electrolyte includes a first solvent, and the first solvent is a carbonate solvent. Specifically, the first solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and ethyl methyl carbonate (EMC). For another example, the first solvent may also include dimethyl carbonate (DMC), diethyl carbonate (DEC), etc.

[0066] The first solvent is a carbonate solvent with low viscosity, high dielectric constant and good electrochemical stability. Low viscosity is conducive to the rapid migration of lithium ions in the electrolyte, and can alleviate the concentration polarization caused by the mismatch between the migration rate of lithium ions in the electrolyte and the migration rate of lithium ions in the positive and negative electrode sheets; a higher dielectric constant is conducive to improving the solubility of lithium salts in the electrolyte, thereby helping to increase the concentration of lithium salts in the electrolyte; good electrochemical stability helps to increase the operating voltage range of lithium-ion batteries and has good compatibility with positive and negative electrodes. Therefore, in this embodiment, by selecting a carbonate solvent as the first solvent for a fast-charge lithium-ion battery, the solubility of lithium salts can be increased and the viscosity of the electrolyte can be reduced, thereby improving the concentration polarization of the fast-charge lithium-ion battery and helping to improve its cycle performance.

[0067] In one embodiment, the electrolyte includes a second solvent, and the second solvent is a carboxylic acid ester solvent. Specifically, the second solvent includes R1-COO-R2, wherein R1 and R2 independently include at least one of an alkyl group having 1 to 5 carbon atoms and a halogenated alkyl group having 1 to 5 carbon atoms.

[0068] For example, R1-COO-R2 may be methyl acetate (MA) or ethyl acetate (EA).

[0069] Carboxylate solvents have lower density and viscosity, and higher ionic conductivity. Lower density can help reduce the overall density of the electrolyte, thereby improving the concentration polarization of the fast-charge lithium-ion battery in the direction of gravity; lower viscosity and higher ionic conductivity are conducive to the rapid migration of lithium ions in the electrolyte, thereby improving concentration polarization. Therefore, in this embodiment, by selecting a carboxylate solvent as the second solvent of the fast-charge lithium-ion battery in combination with the first solvent, the density of the electrolyte can be reduced and the ionic conductivity of the electrolyte can be increased, thereby improving the concentration polarization of the fast-charge lithium-ion battery and helping to improve its cycle performance.

[0070] In one embodiment, the mass content X of the first solvent in the electrolyte satisfies: 20%≤X≤30%.

[0071] In one embodiment, the mass content Y of the second solvent in the electrolyte satisfies: 20%≤Y≤60%.

[0072] Therefore, by adjusting the ratio of the first solvent to the second solvent, the conductivity and density of the electrolyte can be indirectly controlled so that the conductivity and density of the electrolyte are within a suitable range.

[0073] It should be understood that the electrolyte may include other solvents in addition to the first solvent and the second solvent, such as nitrile solvents, sulfone solvents, ionic liquids, and the like.

[0074] In one embodiment, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0075] In one embodiment, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of lithium bis(fluorosulfonyl)imide in the lithium salt of the electrolyte is less than or equal to 30%. The above concentration ratio is obtained by dividing the concentration of lithium bis(fluorosulfonyl)imide in the electrolyte by the concentration of all lithium salts in the electrolyte.

[0076] Specifically, lithium bis(fluorosulfonyl)imide has a higher solubility in carbonate solvents, and has a higher conductivity and lithium ion migration number than lithium hexafluorophosphate. Therefore, by selecting lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide as lithium salts, the solubility of lithium salts in the electrolyte including the aforementioned solvents can be further improved, so that the electrolyte has a higher lithium salt concentration, thereby improving concentration polarization. At the same time, considering that lithium bis(fluorosulfonyl)imide is corrosive to lithium foil, therefore, by controlling the concentration ratio of lithium bis(fluorosulfonyl)imide, its corrosion to the positive electrode sheet can be effectively suppressed.

[0077] It should be understood that the concentration ratio of lithium bis(fluorosulfonyl)imide can be achieved by controlling the molar mass of various lithium salts in the electrolyte. In addition, by adjusting the concentration of lithium salts in the electrolyte, the conductivity and density of the electrolyte can also be adjusted.

[0078] In one embodiment, the conductivity σ of the electrolyte satisfies: 13 mS / cm≤σ≤20 mS / cm.

[0079] In one embodiment, the viscosity μ of the electrolyte satisfies: 2.2 cP≤μ≤2.7 cP.

[0080] In one embodiment, the lithium-ion battery includes a negative electrode plate, the negative electrode plate includes a negative electrode film layer; the single-side coating weight CW of the negative electrode film layer on the negative electrode plate satisfies: 0.06 mg / mm 2 ≤CW≤0.13 mg / mm 2 ; Optionally, 0.08 mg / mm 2 ≤CW≤0.11 mg / mm 2 .

[0081] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector. The coating weight CW is the coating weight per unit area on one surface of the negative electrode current collector.

[0082] In one embodiment, the compaction density PD of the negative electrode film layer satisfies: 1.4 g / cc≤PD≤1.75 g / cc; optionally, 1.5 g / cc≤PD≤1.65 g / cc.

[0083] Specifically, in the preparation process of lithium-ion batteries, considering design parameters such as energy density, the pole piece will undergo a rolling process to make the film layer on the pole piece have a compaction density. The compaction density of the film layer is closely related to the particle morphology, particle size distribution, specific surface area of ​​the active material itself, as well as the proportion of each component in the coated slurry, coating weight, thickness of the current collector and other factors. The compaction density is of great significance to the capacity, rate, cycle and other performances of lithium-ion batteries.

[0084] The compaction density of the film layer PD = pole piece surface density / (pole piece thickness - current collector thickness). The pole piece surface density refers to the mass of the film layer per unit area.

[0085] In one embodiment, the lithium-ion battery includes a positive electrode sheet, the positive electrode sheet includes a positive electrode film layer; the single-sided coating weight CW' of the positive electrode film layer on the positive electrode sheet satisfies: 0.13 mg / mm 2 ≤CW'≤0.29 mg / mm 2 ; Optionally, 0.19 mg / mm 2 ≤CW'≤0.26 mg / mm 2 .

[0086] In one embodiment, the compaction density PD' of the positive electrode film layer satisfies: 2.5 g / cc≤PD'≤2.9 g / cc; optionally, 2.6 g / cc≤PD'≤2.8 g / cc.

[0087] In one embodiment, the volume energy density VED of the lithium-ion battery satisfies: VED ≥ 400 Wh / L.

[0088] That is to say, in addition to the fast charging capability, the lithium-ion battery of the present application is also designed to have a high volume energy density. In other words, the fast-charging lithium-ion battery also has a high volume energy density and has a wide range of application prospects. The high volume energy density of lithium-ion batteries can be achieved by controlling the loading amount of its active material and the compaction density of the positive and negative electrode sheets.

[0089] For high energy density lithium ion batteries, the amount of active material loaded on the positive and negative pole pieces is usually greater than that of ordinary lithium ion batteries, resulting in thicker positive and negative pole pieces, and more serious polarization in the thickness direction of the positive and negative pole pieces during fast charging. The lithium ion battery provided in the embodiment of the present application can enable a lithium ion battery with high volume energy density to have fast charging capability and good cycle performance by controlling fast charging conditions and providing an electrolyte that is compatible with fast charging conditions.

[0090] Next, the positive electrode plate, negative electrode plate, separator and electrolyte in the above-mentioned fast-charging lithium-ion battery are introduced in detail.

[0091] [Electrolyte] Some properties of the electrolyte in the lithium-ion battery of the present application have been partially mentioned in the foregoing text. Next, the electrolyte will be introduced in more detail.

[0092] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The electrolyte mainly includes electrolyte salt and solvent. In lithium-ion batteries, the electrolyte salt is mainly lithium salt. In addition, the electrolyte salt may also include some other additives.

[0093] The selection of lithium salt has been introduced in the previous article and will not be repeated here.

[0094] In one embodiment, the solvent may include at least one of ethylene carbonate, propylene carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone in addition to the examples mentioned above.

[0095] As mentioned above, the mass content X of the first solvent in the electrolyte satisfies: 20%≤X≤30%, and the mass content Y of the second solvent in the electrolyte satisfies: 20%≤Y≤60%.

[0096] Specifically, X can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or a value within the range obtained by combining any two of the above values. Y can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or a value within the range obtained by combining any two of the above values.

[0097] As mentioned above, the conductivity σ of the electrolyte satisfies: 13 mS / cm≤σ≤20 mS / cm. The viscosity μ of the electrolyte satisfies: 2.2 cP≤μ≤2.7 cP.

[0098] Specifically, σ can be 13 mS / cm, 14 mS / cm, 15 mS / cm, 16 mS / cm, 17 mS / cm, 18 mS / cm, 19 mS / cm, 20 mS / cm, or its value is within the range obtained by combining any two of the above values. M can be 2.2 cP, 2.3 cP, 2.4 cP, 2.5 cP, 2.6 cP, 2.7 cP, or its value is within the range obtained by combining any two of the above values. In this embodiment, by selecting the solvent and the lithium salt, and controlling the lithium salt concentration and the solvent ratio, the conductivity and viscosity of the electrolyte can meet the above ranges.

[0099] In one embodiment, the electrolyte also includes additives, which may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high or low temperature performance of the battery, etc.

[0100] [Negative electrode] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material.

[0101] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0102] In one embodiment, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0103] In one embodiment, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0104] As mentioned above, the single-sided coating weight CW of the negative electrode film on the negative electrode sheet satisfies: 0.06 mg / mm 2 ≤CW≤0.13 mg / mm 2 ; Optionally, 0.08 mg / mm 2 ≤CW≤0.11 mg / mm 2 The compaction density PD of the negative electrode sheet satisfies: 1.4 g / cc≤PD≤1.75 g / cc; optionally, 1.5 g / cc≤PD≤1.65 g / cc.

[0105] Specifically, CW can be 0.06 mg / mm 2 , 0.07 mg / mm 2 , 0.08 mg / mm 2 , 0.09 mg / mm 2 , 0.1mg / mm 2 , 0.11 mg / mm 2 , 0.12 mg / mm 2 , 0.13 mg / mm 2 , or its value is within the range obtained by combining any two of the above values. PD can be 1.4 g / cc, 1.45 g / cc, 1.5 g / cc, 1.55 g / cc, 1.6 g / cc, 1.65 g / cc, 1.7 g / cc, 1.75 g / cc, or its value is within the range obtained by combining any two of the above values.

[0106] In the introduction to lithium-ion batteries, lithium-ion batteries have not only fast charging capabilities, but also high volume energy density. Therefore, the coating weight of the negative electrode film layer needs to meet the above range so that the lithium-ion battery has the corresponding volume energy density. In addition, considering that a larger coating weight may cause the thickness of the negative electrode film layer to be thicker, and the thickness of the negative electrode film layer has a certain influence on the fast charging ability of the lithium-ion battery, the reason is that: the smaller the thickness of the negative electrode film layer, the more conducive to the diffusion and infiltration of the electrolyte, which can reduce the concentration polarization in the thickness direction of the negative electrode sheet, reduce the risk of lithium precipitation of the negative electrode sheet when charging with a large current, and contribute to the charging capacity of the lithium-ion battery. Therefore, the compaction density of the negative electrode sheet is designed to meet the above range. The reason is that the fast charging capacity of the lithium-ion battery is not only affected by the thickness of the negative electrode film layer, but also by the porosity. Generally speaking, the smaller the compaction density of the negative electrode sheet, the greater the porosity of the negative electrode film layer, the more conducive to the diffusion and infiltration of the electrolyte, the smaller the concentration polarization, and the better the charging capacity of the lithium-ion battery. Therefore, when the coating weight of the negative electrode film layer is large, the compaction density of the negative electrode sheet can be controlled within an appropriate range, and the negative electrode film layer can have an appropriate porosity. Combined with the electrolyte with a high lithium salt concentration and low density mentioned above, the fast-charge lithium-ion battery can have good cycle performance and high volume energy density.

[0107] When the negative electrode film layer is controlled to satisfy the above-mentioned thickness and load, it is equivalent to taking into account the porosity and thickness of the negative electrode film layer at the same time, which enables the lithium-ion battery to have both better charging capacity and energy density.

[0108] In one embodiment, the negative electrode film layer further includes a binder, which can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0109] In one embodiment, the negative electrode film layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0110] In one embodiment, the negative electrode film layer further includes other additives, such as a thickener (eg sodium carboxymethyl cellulose (CMC-Na)).

[0111] In one embodiment, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet are formed into a negative electrode slurry. For example, the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a negative electrode slurry. Then, the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0112] [Positive electrode] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.

[0113] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0114] In one embodiment, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0115] In one embodiment, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and at least one of its modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The battery is accompanied by the deintercalation and consumption of Li during the charging and discharging process, and the molar content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle. In the enumeration of positive electrode active materials in this application, the molar content of O is only an ideal state value. The release of lattice oxygen will cause the molar content of O to change, and the actual molar content of O will fluctuate.

[0116] As mentioned above, the single-sided coating weight CW' of the positive electrode film on the positive electrode sheet satisfies: 0.13 mg / mm 2 ≤CW'≤0.29 mg / mm 2 ; Optionally, 0.19 mg / mm 2 ≤CW'≤0.26 mg / mm 2 The compaction density PD' of the positive electrode sheet satisfies: 2.5 g / cc≤PD'≤2.9 g / cc; optionally, 2.6 g / cc≤PD'≤2.8 g / cc.

[0117] Specifically, CW' can be 0.13 mg / mm 2 , 0.14 mg / mm 2 , 0.15 mg / mm 2 , 0.16 mg / mm 2 , 0.17mg / mm 2 , 0.18 mg / mm 2 , 0.19 mg / mm 2 , 0.20 mg / mm 2 , 0.21 mg / mm 2 , 0.22 mg / mm 2 , 0.23 mg / mm 2 , 0.24 mg / mm 2 , 0.25 mg / mm 2 , 0.26 mg / mm 2 , 0.27 mg / mm2 , 0.28 mg / mm 2 , 0.29 mg / mm 2 , or its value is within the range obtained by combining any two of the above values. PD' can be 2.5 g / cc, 2.55 g / cc, 2.6 g / cc, 2.65 g / cc, 2.7 g / cc, 2.75 g / cc, 2.8 g / cc, 2.85 g / cc, 2.9 g / cc, or its value is within the range obtained by combining any two of the above values.

[0118] In one embodiment, the positive electrode film layer further includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0119] In one embodiment, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0120] In one embodiment, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet are respectively formed into positive electrode slurries. For example, the first positive electrode active material and / or the second positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry. Then, the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0121] [Isolator] In one embodiment, the battery further includes a separator. The present application has no particular limitation on the type of separator, for example, any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0122] In one embodiment, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0123] In one embodiment, the negative electrode sheet, the positive electrode sheet and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0124] In one embodiment, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0125] In one embodiment, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0126] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 100 is a square structure as an example.

[0127] It should be understood that the battery cell 100 may be the lithium-ion battery in the aforementioned embodiment.

[0128] Figure 2 2 is a battery module 200 as an example. Figure 2 In the battery module 200, the plurality of battery cells 100 may be arranged in sequence along the length direction of the battery module 200. Of course, they may also be arranged in any other manner. The plurality of battery cells 100 may further be fixed by fasteners. The plurality of battery cells 100 may be battery cells 100 of the same chemical system or battery cells 100 of different chemical systems.

[0129] Optionally, in one embodiment, the battery module 200 may further include a housing having an accommodation space, and the plurality of battery cells 100 are accommodated in the accommodation space.

[0130] Optionally, in one embodiment, the battery modules 200 may also be assembled into a battery. The number of battery modules 200 contained in the battery may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery.

[0131] Figure 3 and Figure 4 300 is an example of a battery pack. Figure 3 and Figure 4 The battery pack 300 may include a battery box and a plurality of battery modules 200 disposed in the battery box. The battery box includes an upper box body 301 and a lower box body 302. The upper box body 301 can cover the lower box body 302 and form a closed space for accommodating the battery modules 200. The plurality of battery modules 200 may be arranged in the battery box in any manner.

[0132] It should be understood that the battery cells 100 may first form the battery module 200, and the battery pack 300 may be formed by the battery module 200. Alternatively, the battery pack 300 may be directly formed by the battery cells 100, omitting the intermediate form of the battery module 200.

[0133] In addition, the present application also provides an electrical device, which includes the lithium-ion battery in the aforementioned embodiment.

[0134] In another embodiment, the power-consuming device includes at least one of the battery cell 100, battery module 200, or battery pack 300 provided in the present application. The battery cell 100, battery module 200, or battery pack 300 can be used as a power source for the power-consuming device, or as an energy storage unit for the power-consuming device. The power-consuming device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0135] As an electric device, the number of battery cells 100, battery modules 200, or battery packs 300 can be selected according to its usage requirements.

[0136] As an example of an electric device, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module may be used.

[0137] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0138] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0139] [Examples 1-14 and Comparative Examples 1-2] Example 1 (1) Preparation of negative electrode sheet The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are dissolved in the solvent deionized water according to the mass ratio of 96:0.5:2.5:1, and mixed evenly to obtain the negative electrode slurry. Then the negative electrode slurry is evenly coated on the negative electrode current collector copper foil. After drying, rolling and cutting, the negative electrode sheet is obtained. Among them, the coating weight of the negative electrode film on the negative electrode sheet is CW=0.104 mg / mm 2 , the compaction density of the negative electrode sheet is PD = 1.6 g / cc.

[0140] (2) Preparation of positive electrode The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride, and the conductive agent acetylene black are dissolved in the solvent N-methylpyrrolidone at a mass ratio of 97:2:1, and mixed evenly to obtain the positive electrode slurry. Then the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil. After drying, rolling, and cutting, the positive electrode sheet is obtained. Among them, the coating weight of the positive electrode film on the positive electrode sheet is CW'=0.23 mg / mm 2 , the powder compaction density of the positive electrode sheet is PD'=2.7 g / cc.

[0141] (3) Preparation of electrolyte In an argon atmosphere glove box with a water content of less than 10 ppm, an electrolyte is prepared. The specific process is: the first solvent ethylene carbonate (EC), the second solvent (EA), and dimethyl carbonate (DMC) are mixed evenly in a mass ratio of 30:40:30, and then an appropriate amount of lithium salt lithium hexafluorophosphate (LiPF6) is slowly added thereto, and stirred until completely dissolved. The lithium salt concentration in the electrolyte is c=1.3 mol / L, the density of the electrolyte ρ=1.171 g / mL, the mass content of the first solvent in the electrolyte X=30%, and the mass content of the second solvent in the electrolyte Y=40%. The conductivity σ of the electrolyte of Example 1 is measured to be 17.1 mS / cm, and the viscosity μ=2.54 cP.

[0142] (4) Preparation of lithium-ion batteries The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order so that the isolation film is located between the positive electrode sheet and the negative electrode sheet and can isolate the positive electrode sheet from the negative electrode sheet; then the stacked components are wound and placed in a square aluminum shell, and the electrolyte is injected after drying. After packaging, standing, and formation, the lithium-ion battery of Example 1 is obtained.

[0143] The volume energy density VED of the lithium-ion battery of Example 1 is measured to be 415 Wh / L. It can be seen that the lithium-ion battery is a lithium-ion battery with high energy density. For the lithium-ion battery, the charging time can be designed by performing a rate test on the lithium-ion battery. The specific process is: remove the positive and negative pole pieces of the lithium-ion battery in Example 1, soak and clean them with DMC solvent for more than 72 h, wait for the solvent, lithium salt and additive of the electrolyte to be completely leached, dry the pole pieces in a vacuum oven, and then assemble the positive and negative pole pieces into a laminated three-electrode battery cell, in which the copper wire is used as a reference electrode. A series of different charging rates are set, and the laminated three-electrode battery cell is charged at different charging rates at 25 ° C, and the reference electrode potential is reduced to 0 mV at each charging rate. Cut off, thereby, the SOC corresponding to different charging rates can be measured. When the reference electrode potential drops below 0 mV, the battery will continue to be charged, lithium precipitation will occur, and it cannot be used subsequently. Therefore, the different SOCs obtained by the above method means that the charging rate corresponding to the SOC is the maximum charging rate of the lithium-ion battery under the SOC. According to the data fitting of the maximum charging rate corresponding to different SOCs, the relationship curve between SOC and maximum charging rate can be obtained. Exemplarily, the above method can be used to take 5% SOC as a point, corresponding to a maximum charging rate under the SOC, such as 5% SOC, 10% SOC, 15% SOC to 100% SOC, and the maximum charging rate with the largest value under 10% SOC to 80% SOC can be obtained by fitting the relationship curve between the two data. In the actual charging process, for reasons of battery safety, service life and other factors, the maximum charging rate will not be used directly for charging, but the maximum charging rate multiplied by 0.8 will be used as the charging rate during actual use. Therefore, the equivalent current density of the lithium-ion battery of Example 1 charged from 10% SOC to 80% SOC can be considered as 0.8 multiplied by the maximum charging rate with the largest value.

[0144] In the process of calculating the equivalent current density based on the charging time, it has been mentioned that the charging time for lithium ions to charge from 0% SOC to 100% SOC at 1C is 60 min. Therefore, based on the proportional relationship between the equivalent current density and the charging time, the charging time of the lithium ion battery of Example 1 can also be calculated.

[0145] Based on the above test and derivation process, the fast charging capability of the lithium-ion battery of Example 1 is: the charging time t=11.6 min from 10% SOC to 80% SOC.

[0146] The lithium-ion battery of Example 1 was placed on a charging pile, and the charging time from 10% SOC to 80% SOC was tested (refer to the test method below), and t was measured to be about 11.6 min (with an error of less than 1 min). In Table 1, it is calculated as about 11.6 min, that is, "~11.6".

[0147] Example 2 Compared with Example 1, in the lithium ion battery of Example 2, c=1.0 mol / L, ρ=1.138 g / mL, σ=16.5mS / cm, μ=2.36 cP. The charging time of the lithium ion battery of Example 2 was tested, and t was also measured to be around 11.6 min (with an error of less than 1 min). In other words, the lithium ion battery of Example 2 is also a fast-charging lithium ion battery.

[0148] Example 3 Compared with Example 1, in the lithium ion battery of Example 3, c=1.2 mol / L, ρ=1.152 g / mL, σ=16.7 mS / cm, μ=2.41 cP. Similar to Example 2, the t of the lithium ion battery of Example 3 is also about 11.6 min, which is a fast-charge lithium ion battery.

[0149] Example 4 Compared with Example 1, in the lithium ion battery of Example 4, c=1.6 mol / L, ρ=1.203 g / mL, σ=17.0 mS / cm, μ=2.68 cP. The t of the lithium ion battery of Example 4 is also about 11.6 min, which is a fast-charge lithium ion battery.

[0150] Example 5 Compared with Example 1, in the lithium ion battery of Example 5, c=1.8 mol / L, ρ=1.23 g / mL, t=XX min, σ=16.3 mS / cm, μ=2.75 cP. The t of the lithium ion battery of Example 5 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0151] Example 6 Compared with Example 1, in the lithium ion battery of Example 6, the first solvent is a mixture of EMC and EC, the volume ratio of the two is 2:8, the second solvent is MA, ρ=1.165 g / mLσ=17.0 mS / cm, μ=2.48 cP. The t of the lithium ion battery of Example 6 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0152] Example 7 Compared with Example 1, in the lithium ion battery of Example 7, X=20%, ρ=1.167 g / mL, σ=16.8 mS / cm, and μ=2.49 cP. The t of the lithium ion battery of Example 7 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0153] Example 8 Compared with Example 1, in the lithium ion battery of Example 8, X=25%, ρ=1.169 g / mL, σ=17.0 mS / cm, and μ=2.52 cP. The t of the lithium ion battery of Example 8 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0154] Example 9 Compared with Example 1, in the lithium ion battery of Example 9, Y=20%, ρ=1.182 g / mL, σ=16.0 mS / cm, and μ=2.43 cP. The lithium ion battery of Example 9 was subjected to a rate test with reference to Example 1, and t=12.9 min was calculated. The lithium ion battery of Example 9 was subjected to a charging time test, and t was measured to be about 12.9 min (with an error of less than 1 min).

[0155] Example 10 Compared with Example 1, in the lithium ion battery of Example 10, Y=60%, ρ=1.169 g / mL, σ=17.9 mS / cm, and μ=2.38 cP. The lithium ion battery of Example 10 was subjected to a rate test with reference to Example 1, and t=10.2 min was calculated. The lithium ion battery of Example 10 was subjected to a charging time test, and t was measured to be about 10.2 min (with an error of less than 1 min).

[0156] Embodiment 11 Compared with Example 1, in the lithium ion battery of Example 11, the lithium salt includes LiPF6 and lithium bis(fluorosulfonyl)imide (LiFSI), wherein the concentration of the lithium salt in the electrolyte is still 1.3 mol / L, wherein the concentration of LiPF6 is 0.91 mol / L, the concentration of LiFSI is 0.39 mol / L, and the concentration of LiFSI accounts for 30%; ρ=1.17 g / mL, σ=17.3 mS / cm, μ=2.54cP. The t of the lithium ion battery of Example 11 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0157] Example 12 Compared with Example 11, in the lithium ion battery of Example 12, the concentration of LiPF6 is 1.17 mol / L, the concentration of LiFSI is 0.13 mol / L, and the concentration of LiFSI accounts for 10%; ρ=1.17 g / mL, σ=17.1 mS / cm, μ=2.54 cP. The t of the lithium ion battery of Example 12 is also around 11.6 min, which is a fast-charge lithium ion battery.

[0158] Embodiment 13 Compared with Example 11, in the lithium ion battery of Example 13, the concentration of LiPF6 is 0.65 mol / L, the concentration of LiFSI is 0.65 mol / L, and the concentration of LiFSI accounts for 50%; ρ=1.17 g / mL, σ=17.6 mS / cm, μ=2.53 cP. The t of the lithium ion battery of Example 13 is also around 11.6 min, which is a fast-charging lithium ion battery.

[0159] Embodiment 14 Compared with Example 1, in the lithium ion battery of Example 14, c=1.3 mol / L, X=20%, Y=60%, ρ=1.165g / mL, σ=18.3 mS / cm, μ=2.33 cP. In Example 14, by adjusting the coating surface density, compaction density and other parameters of the positive and negative electrode sheets, a lithium ion battery with a volume energy density VED=406 Wh / L was prepared. Changes in parameters such as coating surface density and compaction density have an impact on the charging capacity of lithium ion batteries. Therefore, referring to Example 1, the lithium ion battery of Example 14 was subjected to a rate test, and t=8.8 min was calculated. The charging time of the lithium ion battery of Example 14 was tested, and t was measured to be around 8.8min (the error was less than 1 min).

[0160] Comparative Example 1 Compared with Example 1, in the lithium ion battery of Comparative Example 1, c=0.8 mol / L, ρ=1.21 g / mL, σ=15.7 mS / cm, and μ=2.21 cP. The t of the lithium ion battery of Comparative Example 1 is also about 11.6 min, which is a fast-charge lithium ion battery.

[0161] Comparative Example 2 Compared with Example 1, in the lithium ion battery of Comparative Example 2, c=1.9 mol / L, ρ=1.242 g / mL, σ=16 mS / cm, μ=2.8 cP. The t of the lithium ion battery of Comparative Example 2 is also around 11.6 min, which is a fast-charge lithium ion battery. Product parameters of Examples 1-14 and Comparative Examples 1-2.

[0162] Table 1: Product parameters of Examples 1-14 and Comparative Examples 1-2

[0163] In Table 1, "lithium salt" represents the type of lithium salt in the electrolyte of lithium-ion batteries, and "c" represents the concentration of lithium salt in the electrolyte. "First solvent" represents the type of the first solvent in the electrolyte, "second solvent" represents the type of the second solvent in the electrolyte, "X" represents the mass content of the first solvent in the electrolyte, "Y" represents the mass content of the second solvent in the electrolyte, "ρ" represents the density of the electrolyte in the lithium-ion battery, "fast charge time" represents the fast charge time measured by the charging time test of the lithium-ion battery, and "number of cycles" represents the number of cycles of the lithium-ion battery at 25°C to 80% SOH (it is generally believed that the battery capacity is consumed to 80% of the rated capacity, and the battery's SOH is 80% SOH).

[0164] Through the analysis and comparison of Examples 1-14 and Comparative Examples 1-2, it can be seen that the cycle performance of Examples 1-14 is significantly better than that of Comparative Examples 1-2, indicating that the use of an electrolyte with high lithium salt concentration and low density in a lithium-ion battery that supports high-current fast charging can effectively improve the concentration polarization during the fast charging process of the lithium-ion battery and enhance the cycle performance of the lithium-ion battery.

[0165] According to the data comparison analysis of Examples 1-5 and Comparative Example 2, as the concentration of lithium salt in the electrolyte increases, the density and viscosity of the electrolyte increase accordingly. In the range of lithium salt concentration of 1.1 mol / L to 1.6 mol / L, the conductivity of the electrolyte experiences a trend of first rising and then falling. The cycle performance of the lithium ion battery of Examples 1-4 improves with the increase of lithium salt concentration. However, the cycle performance of Comparative Example 2 with the largest lithium salt concentration is far less than that of Examples 1-5, and the cycle performance of Example 5 is also less than that of Example 4. Thus, it is shown that increasing the concentration of lithium salt in the electrolyte can effectively improve concentration polarization and improve the cycle performance of lithium ion batteries. However, too large a lithium salt concentration will affect the density, viscosity and conductivity of the electrolyte, and the density, viscosity and conductivity of the electrolyte will affect the dynamics of the lithium ion battery and will also affect the cycle performance of the lithium ion battery. Therefore, taking all factors into consideration, it is more conducive to improving the cycle performance of lithium ion batteries by controlling the lithium salt concentration within a higher and appropriate range. It should be understood that when the electrolyte density is large, it will cause lithium ions to have greater difficulty in "climbing" in the direction of gravity, exacerbating the concentration polarization in the direction of gravity. When the electrolyte density is small, the concentration polarization in the direction of gravity is small. Based on this, although the density data of the electrolyte provided in the data in Table 1 are all large, the scheme of the present application can improve the concentration polarization and enhance the cycle performance of lithium-ion batteries when the electrolyte density is large. Then, when the electrolyte density is small and the concentration polarization is small, it can be inferred without a doubt that the scheme of the present application can also improve the concentration polarization and enhance the cycle performance of lithium-ion batteries.

[0166] The data of Examples 1 and 6 show that different first solvents and second solvents can achieve similar effects when the lithium salt concentration is the same.

[0167] According to the comparative analysis of the data of Examples 1, 7-8, it can be seen that as the mass content of the first solvent increases, the conductivity of the electrolyte also increases, the lithium ion dynamics improve, and the cycle performance improves accordingly. At the same time, the viscosity and density of the electrolyte also increase. It can be seen that the cycle performance of Example 8 is improved by 238 cycles compared to Example 7, while the cycle performance of Example 9 is only improved by 48 cycles compared to Example 8. This shows that the concentration polarization caused by the increase in electrolyte viscosity and density is intensified. This proves that by controlling the mass content of the first solvent within a suitable range, it is helpful to improve the cycle performance of lithium-ion batteries.

[0168] According to the data analysis and comparison of Examples 1, 9-10, it can be seen that as the mass content of the second solvent increases, the density and viscosity of the electrolyte decrease, and the conductivity increases. It is proved that the second solvent can reduce the density and viscosity of the electrolyte and improve the conductivity of the electrolyte. At the same time, the cycle performance of the lithium-ion battery is also improved, but its improvement trend is also gradually slowing down. It is explained that on the basis of the mass content of the first solvent being within a suitable range, by controlling the mass content of the second solvent within a suitable range, it is helpful to improve the cycle performance of the lithium-ion battery. In other words, by adjusting the ratio of the first solvent to the second solvent, the conductivity and density of the electrolyte can be indirectly regulated, so that the conductivity and density of the electrolyte are within a suitable range, and the cycle performance of the lithium-ion battery is comprehensively improved.

[0169] In addition, although the cycle performance is not as good as that of Example 1, the charging time of the lithium-ion batteries of Examples 9-10 is further shortened, indicating that the content of the second solvent improves the lithium-ion kinetics and contributes to the fast charging performance of the lithium-ion battery.

[0170] According to the data analysis and comparison of Examples 11-13, when lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are used, as the concentration of lithium bis(fluorosulfonyl)imide increases, the cycle performance of the lithium-ion battery is further improved. On the other hand, considering the corrosiveness of lithium bis(fluorosulfonyl)imide, and according to the data of Examples 11 and 13, the cycle performance is improved but the trend is significantly slowed down. It shows that by controlling the concentration ratio of lithium bis(fluorosulfonyl)imide within a suitable range, the cycle performance of the lithium-ion battery can be further improved.

[0171] Example 14 demonstrates another energy-dense lithium-ion battery, which, when used with an electrolyte similar to that in the previous examples, achieves a shorter charging time and excellent cycle performance.

[0172] The following is a brief introduction to the test methods of the physical and chemical parameters and performance parameters involved in the embodiments of the present application. It should be understood that the following test methods are only examples, and other test methods known in the art may also be used for testing.

[0173] 1. Test method for electrolyte conductivity The test method is in accordance with HG / T 4067-2015. The conductivity of the electrolyte to be tested is tested with a conductivity meter: about 100 ml of the sample to be tested is taken from a dry, clean, corrosion-resistant sample bottle, and sealed in a constant temperature water bath at 25±0.5 ℃. When the temperature of the sample to be tested is constant, the sample bottle cap is replaced with a rubber stopper with an electrode inserted. When the temperature is within the range of 25±0.5 ℃, the data is read, which is the conductivity of the sample to be tested.

[0174] 2. Molar concentration test method The molar concentration of the lithium salt in the electrolyte can be determined by various methods known to those skilled in the art, such as titration, electrochemical analysis, spectrophotometry, inductively coupled plasma, etc.

[0175] 3. Charging time test method Place the lithium-ion battery to be tested on the charging pile, adjust the state of charge of the lithium-ion battery to 10% SOC (the power is 10% of the rated power), then charge it on the charging pile, and record the time it takes for the lithium-ion battery to be charged to 80% SOC (80% of the rated power), which is the charging time of the lithium-ion battery.

[0176] 4. Test method for volume energy density Place the lithium-ion battery at 25 °C, charge it to 3.8 V at a constant current of 0.33 C, let it stand for 1 min, then charge it to 3.8 V at a constant current of 0.1 C, let it stand for 30 min; discharge it to 2.0 V at a constant current of 0.33 C, and record the discharge capacity A0 at this time, in units of Ah; use a caliper to measure the length, width, and height of the lithium-ion battery, and calculate the volume of the single battery V0, in units of L; the volume energy density of the single battery VED = (A0 × the discharge platform voltage of the lithium-ion battery) / V0, in units of Wh / L. It should be understood that the discharge platform voltage of lithium-ion batteries with different positive and negative electrode systems is different, which can be obtained by testing their charge and discharge curves or referring to existing literature.

[0177] 5. Test method for coating weight Cut the negative electrode sheet to a specified area S, weigh it to obtain a weight m1, wash off the film layer on the surface of the negative electrode current collector, and weigh the weight m2 of the negative electrode current collector. The loading amount of the negative electrode film layer on the negative electrode current collector is (m1-m2) / S.

[0178] 6. Test method for pole piece compaction density Remove the positive and negative pole pieces from the lithium-ion battery and measure the pole piece thickness and current collector thickness respectively. Take a pole piece of a certain area, measure its area and weigh the mass of the film layer on the current collector after removing the current collector, and calculate the pole piece surface density based on the area and mass. Therefore, the compacted density of the pole piece PD = pole piece surface density / (pole piece thickness - current collector thickness).

[0179] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises: An electrolyte, wherein the electrolyte comprises a lithium salt, and a concentration c of the lithium salt in the electrolyte satisfies: c ≥ 1 mol / L; The density ρ of the electrolyte satisfies: 0.9 g / mL≤ρ≤1.23 g / mL; The charging time t of the lithium-ion battery from 10% SOC to 80% SOC satisfies: 8.8 min≤t≤15 min.

2. The lithium-ion battery according to claim 1, characterized in that c≤1.8 mol / L.

3. The lithium-ion battery according to claim 2, characterized in that: 1.1 mol / L≤c≤1.6 mol / L.

4. The lithium-ion battery according to claim 1, characterized in that: 8.8 min≤t≤10 min.

5. The lithium-ion battery according to claim 1, characterized in that: The electrolyte includes a first solvent, and the first solvent includes at least one of ethylene carbonate, propylene carbonate, and ethyl methyl carbonate.

6. The lithium-ion battery according to claim 1, characterized in that The electrolyte includes a second solvent, and the second solvent includes R1-COO-R2, wherein R1 and R2 each independently include one of an alkyl group having 1 to 5 carbon atoms and a halogenated alkyl group having 1 to 5 carbon atoms.

7. The lithium-ion battery according to claim 6, characterized in that: The mass content X of the first solvent in the electrolyte satisfies: 20%≤X≤30%.

8. The lithium-ion battery according to claim 6, characterized in that The mass content Y of the second solvent in the electrolyte satisfies: 20%≤Y≤60%.

9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

10. The lithium ion battery according to claim 9, characterized in that: The lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium bis(fluorosulfonyl)imide in the lithium salt of the electrolyte is less than or equal to 30%.

11. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The conductivity σ of the electrolyte satisfies: 13 mS / cm≤σ≤20 mS / cm.

12. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The viscosity μ of the electrolyte satisfies: 2.2 cP≤μ≤2.7 cP.

13. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The volume energy density VED of the lithium-ion battery satisfies: VED≥400 Wh / L.

14. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The lithium-ion battery comprises a negative electrode plate, and the negative electrode plate comprises a negative electrode film layer; The single-sided coating weight CW of the negative electrode film layer on the negative electrode sheet satisfies: 0.06 mg / mm 2 ≤CW≤0.13 mg / mm 2 .

15. The lithium ion battery according to claim 14, characterized in that: 0.08 mg / mm 2 ≤CW≤0.115 mg / mm 2 。 16. The lithium ion battery according to claim 14, characterized in that: The compaction density PD of the negative electrode film layer satisfies: 1.4 g / cc≤PD≤1.75 g / cc.

17. The lithium ion battery according to claim 16, characterized in that: 1.55 g / cc≤PD≤1.7 g / cc.

18. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The lithium-ion battery comprises a positive electrode sheet, and the positive electrode sheet comprises a positive electrode film layer; The single-sided coating weight CW' of the positive electrode film layer on the positive electrode sheet satisfies: 0.13 mg / mm 2 ≤CW'≤0.29mg / mm 2 .

19. The lithium ion battery according to claim 18, characterized in that 0.19 mg / mm 2 ≤CW’≤0.26 mg / mm 2 。 20. The lithium ion battery according to claim 18, characterized in that The compaction density PD' of the positive electrode film layer satisfies: 2.5 g / cc≤PD'≤2.9 g / cc.

21. The lithium ion battery according to claim 20, characterized in that 2.6 g / cc≤PD'≤2.8 g / cc.

22. An electrical device, characterized in that: The electrical device comprises a lithium-ion battery as claimed in any one of claims 1 to 21.

Citation Information

Patent Citations

  • Lithium ion secondary cell

    CN110165284A

  • Lithium ion battery electrolyte and lithium ion battery

    CN114300750A

  • Lithium ion secondary battery and electric device

    CN116936931A

  • Lithium ion battery and method for judging power performance of lithium ion battery

    CN117254094A

  • Fast charge long-lifetime secondary battery, battery module, battery pack, and power consumption device

    US20230091618A1